Job Loss and Health Spillovers in the Family - Christina Gathmann; Kristiina Huttunen; Laura Jenström; Lauri Saaksvuori; Robin Stitzing (ZBW - Leibniz Information Centre for Economics, 2020)
A sizable literature documents that displaced workers suffer substantial negative consequences in the labor market and health. These effects may extend to the partner or spouse through household decision-making. Using administrative data of all workers and firms matched to mortality and patient records, we document a stunning asymmetry: when a man loses his job in a plant closure, both the man and the spouse suffer negative health consequences. When a woman loses here job, in contrast, we find no such dire health consequences. We explore three explanations for this phenomenon: the role of spousal labor supply, the size of earnings and income losses, and the importance of family structure and gender roles. Spousal labor supply responses are very small despite limited insurance through public transfers. The size of income losses and gender roles seem to play a role for explaining the observed asymmetry.
Keywords: I12; I14; J65; J12; 330